Internalisasi Nilai Budaya pada Pembelajaran Santri di Pondok Pesantren Tradisional - Maskur, Maskur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to describe how the internalization of cultural values ​​in the learning of students in traditional Islamic boarding schools. The research was conducted using a descriptive method based on a qualitative approach. Data collection methods that have been implemented are observation, semi-structured interviews, and documentation studies. Data analysis was performed using an interactive analysis model. To ensure data validity, resource-based and technique-based triangulation was carried out. The results showed that the internalization of cultural values ​​in the learning of santri at traditional pesantren was carried out through the bandongan, sorogan and halaqohan methods. The internalization of cultural values ​​is carried out by integrating the three methods in an integrated manner on two main axes, namely the dormitory axis and the mosque axis which are integrated in one unit. The cultural values ​​implanted in the learning of the students include the values ​​of transcendence, humanization, diversity, liberation and justice. In conclusion, the internalization of cultural values ​​in the learning of santri in traditional Islamic boarding schools is carried out through the bandongan, sorogan and halaqohan methods. Keywords: Internalization, Cultural Values, Santri Learning